Kebudayaan Tabuik sebagai upacara adat di Kota Pairaman Sumatra Barat - Febri Rachmad Arifian; Lutfiah Ayundasari (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial (JIHI3S), 2021)
Culture is the result of the development of human life, and the two things cannot be separated because they are related. The Tabuik culture in Pairaman City, West Sumatra is one of the creations of the development process of human life. Tabuik is a culture that is held every 10th of Muharram, this Tabuik ceremony aims to commemorate the death of the grandson of the Prophet Muhammad S.A.W, namely Hussein bin Ali. This research method is library research with five stages, namely topic selection, source collection, verification, interpretation: analysis and synthesis, then writing. The Tabuik ceremony certainly has a meaning and value that is contained in the ceremony. The meaning of the Tabuik culture itself can be seen from the form of the Tabuik itself, such as the burqa is a symbol of an angel carrying the body of Husein flying, the peak of the tabuik has two meanings, namely as a news carrier and as a protector for all Muslims. The values of the culture are a picture of a combination of custom and religion, so that the values that exist in Tabuik are still not far from religious values. Kebudayaan adalah hasil dari perkembangan hidup manusia, dan kedua hal itu tidak dapat dipisahkan karena saling berhubungan. Kebudayaan Tabuik yang berada pada Kota Pariaman Sumatera Barat adalah salah satu cipataan dari proses perkembangan hidup manusia. Tabuik ialah kebudayaan yang dilaksanakan setiap tanggal 10 Muharram, upacara Tabuik ini bertujuan untuk memperingati wafatnya cucu Nabi Muhammad S.A.W yaitu Hussein bin Ali. Metode penelitian ini adalah library research dengan lima tahapan yaitu pemilihan topik, pengumpulan sumber, verifikasi, interpretasi: analisis dan sintesis, lalu penulisan. Dalam upacara Tabuik pastinya memiliki sebuah makna dan nilai yang terkandung dalam upacara tersebut. Makna dari kebudayaan Tabuik sendiri dapat dilihat dari bentuk Tabuik itu sendiri seperti burqa adalah simbol dari malaikat yang membawa jasad Husein terbang, puncak tabuik memiliki dua makna yaitu sebagai pembawa berita dan sebagai pelindung bagi seluruh umat islam. Adapun nilai-nilai dari kebudayaan tersebut adalah gambaran perpaduan antara adat dan agama, sehingga nilai-nilai yang ada pada dalam Tabuik masih tidak jauh dalam nilai-nilai agama.